The modern concept of diagnosis and treatment of gunshot and mine-explosive injuries of limbs - Loskutov, Oleksandr; Zarutskiy, Yaroslav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Purpose: to analyze medical care experience in the treatment of patients with limb wounds in the system of staged military treatment-evacuation supplying (TES) and to build up recommendation for common understanding in pathogenesis of gunshot and mine-explosing wounds, diagnostic principles and treatment. Methods: medical cases and accompanying documents of patients with wounded limbs treated in the hospital from May 2014 to December 2015. Wounds character, localization, severity, medical care and treatment at the different stages of evacuation were assessed. Results: upper and lower limbs wounds consist 62,5% out of general structure of sanitary loses. Among them 78,4% have soft tissue injuries, 21,6% — gunshot fractures. Characteristic feature of combat wound are the big part of combine and multiple injuries (32,1%), domination of splinter (62,9%) and mine-explosive (25,6%) injuries. The majority of the wounded with isolated and multiple wounds to extremities are slightly injured and represent a significant reserve of military personnel. Combat TES system involves the separation of medical care and treatment of limb wounds into separate stages in conjunction with the evacuation of victims. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;" lang="EN-US">Conclusion: <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">medial care and treatment wounded with limb injuries with gunshot and mine-explosive wounds is providing in the military system of TES. The main goal of treatment of gunshot wounds of extremities is to achieve an uncomplicated wound healing, healing of fractures and limb function recovery.<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">Implementation of the basic TES system tasks is the returning the maximum number of wounded<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> —<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US"> should contribute to the effective organization of staged treatment slightly wounded in hospitals without their frontline evacuation to the rear of the country.